2008
DOI: 10.1098/rspa.2008.0211
|View full text |Cite
|
Sign up to set email alerts
|

On the surface plasmon polariton wave at the planar interface of a metal and a chiral sculptured thin film

Abstract: The solution of a dispersion equation indicates the theoretical existence of multiple modes of surface plasmon polariton wave propagation at the planar interface of a metal and a chiral sculptured thin film (STF). One mode appears to occur over a wide range of the structural period of the chiral STF, while all other modes exist only above some minimum value of the structural period, the minimum value being different for each mode. In order to excite the different modes, the interface can be incorporated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 32 publications
3
59
0
Order By: Relevance
“…The experimental observation of multiple SPR therefore confirms the theoretical predictions. [6][7][8][9] Comments on the angular location and width of SPR dips are discussed by Polo and Lakhtakia. 6 These resonant phenomenon could be used for sensing purposes such as detecting biomolecules of interest for water safety.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental observation of multiple SPR therefore confirms the theoretical predictions. [6][7][8][9] Comments on the angular location and width of SPR dips are discussed by Polo and Lakhtakia. 6 These resonant phenomenon could be used for sensing purposes such as detecting biomolecules of interest for water safety.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, SPPs are excited at noble metal/homogeneous dielectric material interfaces and can be observed only for the parallel polarization of the incident laser beam, p-polarization (the direction of the polarization lies in the plane of incidence). 3 Recent theoretical studies [6][7][8][9] have shown that by replacing the homogeneous dielectric material by a linear, anisotropic dielectric material, more than one SPP wave can be launched, and in the same film SPP waves can also be observed for spolarization of the incident laser beam (the direction of the polarization is perpendicular to the plane of incidence). 6,7 The theoretical basis for the excitation of multiple SPR and excitation by s-polarization is explained by Faryad and Lakhtakia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Truly surprising results were revealed when calculations [4] were directed at SPP waves bound to the interface of a metal and the more complicated chiral STF. Multiple SPP-wave modes of propagation bound to a single interface for a single frequency of excitation were found.…”
mentioning
confidence: 99%